Tren Busana Muslim dalam Perspektif Hukum Islam - Rahmadani, Nur Fitri; Shuhufi, Muhammad; Halim, Fatimah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Muslim fashion trends have experienced significant changes in the last few decades, along with increasing awareness of Islamic identity and the influence of globalization. This article examines Muslim fashion trends from the perspective of Islamic law with a focus on the Sharia principles governing clothing and how the latest trends reflect or challenge these norms. This research uses a qualitative method by using literary analysis from books, journals and other reliable sources. The research results show that despite efforts to adhere to Sharia principles, social and cultural dynamics influence the interpretation and application of Islamic law in Muslim clothing.